Enhancement of Efficiency and Lifetime of Blue Organic Light-Emitting Diodes Using Two Dopants in Single Emitting Layer - Jianning Yu; Na Wei; Chong Li; Bin Wei; Wei Huang; Taiju Tsuboi; Jianhua Zhang; Zhilin Zhang (Advances in Materials Science and Engineering)
We have demonstrated efficient blue organic light-emitting diode with the structure of indium tin oxide/4,4′,4″-tris(N-(2-naphthyl)-N-phenyl-amino)triphenylamine/1,4-bis[N-(1-naphthyl)-N′-phenylamino]-4,4′-diamine/9,10-di(2-naphthyl)anthracene (ADN): 1-4-di-[4-(N,N-di-phenyl)amino]styryl-benzene (DSA-ph) 3 wt%/tris-(8-hydroxyquinoline)aluminum/LiF/Al. Improved efficiencies and longer operational lifetime were obtained by codoping a styrylamine-based dopant BD-3 (0.1 wt%) into the emitting layer of ADN doped with DSA-ph compared to the case of non-codoping. This was due to the improved charge balance and expansion of exciton recombination zone. The better charge balance was obtained by reducing the electron mobility of ADN which was higher than the hole mobility in the case of non-codoping.